Evaluation of phenotypic methods for rapid detection of Methicillin resistant Staphylococcus aureus in a tertiary care hospital - Dr Saba Samreen; Dr Kala Yadhav M.L. (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: MRSA, an important pathogen causing nosocomial and community acquired infections, has posed a serious therapeutic challenge. A faster, cost effective method detecting MRSA is of utmost necessity.Objective: This study was done to look for the prevalence, antimicrobial sensitivity and evaluation of oxacillin E -test with chromogenic agar and cefoxitin disk diffusion methods for rapid detection of MRSA.Methods: A total of 100 isolates of Staphylococcus aureus isolated from clinical samples were included in the study. Antimicrobial susceptibility testing, oxacillin E-test, chromogenic agar inoculations were done as per CLSI guidelines.Results: Out of the 100 isolates, 46% were identified as MRSA by Cefoxitin disk diffusion method. All these isolates were detected by Chromogenic agar within 24hrs. All MRSA strains were resistant to penicillin (100%). MRSA were found to be more multidrug resistant as compared to MSSA. All the strains were sensitive to Vancomycin, Linezolid irrespective of their methicillin status.Conclusion: Chromogenic agar was found to be rapid, easy, sensitive and specific method in detecting MRSA. It is ideal to inoculate sample directly onto Chromogenic agar in clinically suspected Gram positive infections or detected as Gram positive cocci in direct smear. The use of molecular methods for MRSA is largely restricted to reference laboratories and is not utilised in many laboratories as a routine tool. So, rapid and accurate detection of MRSA by Chromogenic agar helps to immediately start the antimicrobial therapy and avoid its spread.